Food habits of adolescents: consumption pattern and relationship with BMI - Brunhoso, Cátia (2014)
Evaluate food habits of adolescents of the northern Portugal using the three-days food diary. Methods: It is a cross-sectional analytical study. Data were collected using a three-days food diary. It was also collected weight and height, and calculated the BMI. The end sample consisting in 40 adolescents. Statistical analysis was made by the application of correlation test between the percentile for BMI/age, nutrients and food portions, through the application of the Spear-man test and the Pearson test, using the software Statistical Package for the Social Sciences, version 20. Results: It was found a significantly correlation betwe-en the consumption of vegetables and fruit (p-value = 0.001), and also between the consumption of vegetables and monounsaturated fats (p-value = 0.000). No significantly correlation was found between the percentile of BMI and food consumption. Conclusion: It was found a healthy eating pattern of the adolescents by the correlation between the consumption of vegetables with fruits and monounsaturated fats. The availability of this type of food in school is a good justifi-cation for that consumption. This pattern fits in with the traditional diet of Mediterranean countries, which includes Portugal. There is a large advantage in this diet namely the consumption of olive oil, which is associated with large benefits on health.